Herbeno / Mohd Izwan Abu Bakar, Nuur Aina Farhana Ahmad Rosli and Siti Nurfaten Abu Bakar - Abu Bakar, Mohd Izwan; Ahmad Rosli, Nuur Aina Farhana; Abu Bakar, Siti Nurfaten (2018)
With more people than ever living in the cities, how do we reconcile our need for fresh fruit and vegetables with the challenges of life in an urban environment where the time and space for gardening are limited? This study was conducted to develop a product that is fully automatic to harvest seed with everything at your fingertips and you literally don't have to do a thing. It also discovers how many potential consumers are interested in the product. Also, this paper will highlight the design of the product and reasoning behind the parameters chosen.